2023
DOI: 10.3390/coatings13101708
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficient Gas Nitridation of AISI 316L Austenitic Stainless Steel by a Novel Critical Temperature Nitriding Process

Daodong Tang,
Chengsong Zhang,
Haoting Zhan
et al.

Abstract: To improve the surface properties of austenitic stainless steels, a thick S-phase layer was prepared by using a novel critical temperature nitriding (CTN) process. The properties of the thick S-phase layer were optimized by controlling the process parameters. The microstructures and phase compositions of CTN-treated layers were characterized by the optical microscope, scanning electron microscope and X-ray diffraction, respectively. The surface properties, including corrosion and wear resistance, were systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The chemical stripping process can be considered as a redox reaction that occurs on the surface of the AlSiY coating. The higher the EWF is, the harder it is to oxidize [20]. Additionally, there exists galvanic corrosion between surfaces with different EWFs.…”
Section: Explanation Of Uniform Stripping By First-principles Calcula...mentioning
confidence: 99%
“…The chemical stripping process can be considered as a redox reaction that occurs on the surface of the AlSiY coating. The higher the EWF is, the harder it is to oxidize [20]. Additionally, there exists galvanic corrosion between surfaces with different EWFs.…”
Section: Explanation Of Uniform Stripping By First-principles Calcula...mentioning
confidence: 99%
“…Research on iron-based thermally sprayed coatings has shown promising results in various applications. Consequently, several stainless steel alloys have shown good corrosion properties, especially when they were exposed to cavitation erosion conditions [7][8][9][10]. De et al [11] in their research demonstrated that 304 stainless steel stands out as an outstanding material resistant to cavitation, offering significant application potential across various fields.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to its favorable characteristics, including good plasticity, high corrosion resistance and cost effectiveness. Also, the martensitic steels [3,9,10] have demonstrated outstanding resistance to cavitation erosion, and this performance was closely associated with their hardness. Nevertheless, in numerous instances, softer austenitic or dual-phase steels have proven to be even more advantageous, primarily because of their superior strain hardening properties [3,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the nitriding of austenitic stainless steel with the aim of increasing its tribological properties has been developed [1][2][3]. Here, nitrogen insertion in the temperature range between 300 and 450 • C leads to a super-saturated phase with nitrogen still in solid solution [4][5][6][7][8][9]. This so-called expanded austenite is a metastable phase which can accommodate nitrogen up to 38 at.%, resulting in anisotropic lattice expansion up to 12% [10].…”
Section: Introductionmentioning
confidence: 99%